PERAN MEDIA MASSA DALAM INTERNALISASI NILAI-NILAI AGAMA UNTUK MENGEMBANGKAN PENDIDIKAN KARAKTER DAN BUDAYA BANGSA - Ambarwati Ambarwati (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2014)
This paper is to analyse the content of the newspapers published in Central Java, such as Suara Merdeka, Jateng Pos and Warta Jateng, in their role of giving information and education about religious values in building children’s character. This is driven by the fact that a lot of deviances were made by students, such as fight among students and criminal gangs in school. This is one of the indicators that character education is not enough to be taught only at school through curriculum. Therefore, newspapers play a role in that purpose. The research shows the newspapers play a role as information provider, educator, persuasive communicator, cultural transmitter, correlator, and social testator. In the meantime, character education is categorised into: practicing religious teachings, having good ethic and morality, understanding religious norms, doing mutual respect, having tolerance towards others, cooperating in social and national life.